Image-guided Sports Medicine and Musculoskeletal Tumor Interventions: A Patient-Centered Model - Dalili, Danoob; Isaac, Amanda; Rashidi, Ali; Åström, Gunnar; Fritz, Jan (Seminars in Musculoskeletal Radiology, 2020)
The spectrum of effective musculoskeletal (MSK) interventions is broadening and rapidly evolving. Increasing demands incite a perpetual need to optimize services and interventions by maximizing the diagnostic and therapeutic yield, reducing exposure to ionizing radiation, increasing cost efficiency, as well as identifying and promoting effective procedures to excel in patient satisfaction ratings and outcomes. MSK interventions for the treatment of oncological conditions, and conditions related to sports injury can be performed with different imaging modalities; however, there is usually one optimal image guidance modality for each procedure and individual patient. We describe our patient-centered workflow as a model of care that incorporates state-of-the-art imaging techniques, up-to-date evidence, and value-based practices with the intent of optimizing procedural success and outcomes at a patient-specific level. This model contrasts interventionalist- and imaging modality-centered practices, where procedures are performed based on local preference and selective availability of imaging modality or interventionalists. We discuss rationales, benefits, and limitations of fluoroscopy, ultrasound, computed tomography, and magnetic resonance imaging procedure guidance for a broad range of image-guided MSK interventions to diagnose and treat sports and tumor-related conditions.
Keywords: sports; tumor; intervention; magnetic resonance imaging guidance; computed tomography; ultrasound